Social Class Representation in the Indonesian translation of Normal People: A Study of Domestication and Foreignization - Dhio Muhammad Al Dicky; Dadan Rusmana; Agry Pramita (Universitas Muhammadiyah Barru, 2026)
This study examines the representation of social class in the Indonesian translation of Sally Rooney’s Normal People through the application of domestication and foreignization strategies. Although traslation studies have widely examined linguistic and cultural aspects, the issues of how social class is reshaped through translation especially in the Indonesian context has received relatively little attention. This research aims to address that gap by combining sociological perspectives with translation analysis. Grounded in qualitative research design, the study analyzes twelve selected excerpts from a total of 52 identified instances that portray class distinctions in terms of family background, economic conditions, education, and social relationships. The data consist of source texts and their corresponding target texts, collected through close reading and categorized based on social class indicators and translation strategies. The analysis is informed by Karl Marx’s theory of class, Max Weber’s concept of status and symbolic capital, as well as Lawrence Venuti’s framework of translation strategies. The results indicate that domestication is used more frequently, making the text more accessible to Indonesian readers. However, this tendency also leads to a simplification of class differences and may lessen the critical portrayal of inequality. Foreignization appears selectively, particularly in references to elite institutions and lifestyles, functioning to preserve symbolic capital associated with upper-class culture. This study contributes to translation studies by demonstrating how translation strategies shape the transmission of social class ideology across cultures and highlights the translator’s role in mediating social meanings.